If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15z + 3 + -9z = 0 Reorder the terms: 3 + 15z + -9z = 0 Combine like terms: 15z + -9z = 6z 3 + 6z = 0 Solving 3 + 6z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6z = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 6z = 0 + -3 6z = 0 + -3 Combine like terms: 0 + -3 = -3 6z = -3 Divide each side by '6'. z = -0.5 Simplifying z = -0.5
| -9b-10=62 | | 2(x-8)-4(3x+6)=30 | | 12x+4x+7-5x=8+(-5)(5x-6x)+23 | | y=-5(2)-2 | | 16w-14=18w | | 5x^2-20x-5=0 | | 3x^3+4x^2=27x+36 | | y=-5(1)-2 | | y=-5(0)-2 | | -2x-18=-12x+4x | | y=-5(-1)-2 | | 6x-9-9x-4=2x+12 | | y=10(5)+2 | | 2(x-3)-5=x+5 | | 4x^2+32-36=0 | | y=10(1)+2 | | y=10(0)+2 | | y=10(-1)+2 | | 9-28x-32x=x-3 | | -2(7y+5)= | | 9h^2-4j^2= | | 18x-21x=12-x | | y=-2(-2)+4 | | 4x+18=7x+21 | | y=-2(-4)+4 | | (Y-4)-(y+7)=5y | | y=5(2)-3 | | y=5(1)-3 | | 16x-16=12x+36 | | y=5(0)-3 | | y=5(-1)-3 | | 12x=35+5x |